2009
DOI: 10.1016/j.appet.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived healthiness of food. If it's healthy, you can eat more!

Abstract: 1The main aim of this study was to investigate the effects of food-related beliefs 2 about the healthiness of foods, restrained eating, and weight salience on actual food intake 3 during an ad libitum snack. In a 2 (healthy vs. unhealthy) by 2 (restrained vs. unrestrained 4 eaters) by 2 (weight salient vs. not salient) factorial design, 99 female undergraduate 5 students were invited to taste and rate oatmeal-raisin cookies. Dietary restraint and weight 6 salience did not influence snack intake, but participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
147
6
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(163 citation statements)
references
References 23 publications
6
147
6
4
Order By: Relevance
“…It was shown recently that when people think that they consume a healthy snack, they consume 35% more than when the snack is perceived as unhealthy. 33 A similar phenomenon may have occurred in this study, in which subjects perceived LED snacks as healthy and as a result they were not preoccupied with the energy content of these snacks.…”
Section: Discussionmentioning
confidence: 72%
“…It was shown recently that when people think that they consume a healthy snack, they consume 35% more than when the snack is perceived as unhealthy. 33 A similar phenomenon may have occurred in this study, in which subjects perceived LED snacks as healthy and as a result they were not preoccupied with the energy content of these snacks.…”
Section: Discussionmentioning
confidence: 72%
“…Older children, who process information in a more complex manner (John 1999), acquire information differently (Peracchio 1992), and rely less on taste when making food decisions due to higher self-control, might show different effects on consumption. Moreover, although we know a great deal about the effect of making food instrumental to health goals on adults' consumption, such that in some cases it decreases consumption (Raghunathan, Naylor, and Hoyer 2006) but in other cases it increases consumption (Provencher, Polivy, and Herman 2008;Wansink and Chandon 2006), especially among dieters (Irmak, Vallen, and Robinson 2011), it is not clear how making food instrumental to a nonhealth goal would affect adults' consumption. To the extent that adults serve food to children and decide how to present the food to them, understanding how adults react to such messages is important.…”
Section: Alternative Explanations and Future Researchmentioning
confidence: 99%
“…Many consider that 100 g/100 ml best serves as a comparator between foods that are often presented in a range of different portion sizes, whereas others argue that a food containing high levels of an 'unhealthy' nutrient 'per 100 g' may only make a small negative contribution to a person's diet if the 'typical' portion for that food is much smaller than 100 g. 13 Product category associations (e.g., nutrition value of chocolate versus yogurt) have been shown to be one of the cues used by consumers to form judgements about a product's healthfulness. 15,16 On the basis of the evaluability principle, it is also argued that 'numerical [nutrient content] information lacks meaning by itself and has to be compared with other information to be interpreted meaningfully'. 17 In other words, a comparison baseline, for example a Guideline Daily Amount (GDA), may be essential for the processing of numerical nutrition information.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 Foods are often categorised as 'healthy' or 'diet'; and it has been shown that foods considered part of a 'healthy' category can elicit a systematic underestimation of their energy content, resulting in higher intake quantities regardless of the portion size. 16,19 This study explores to what extent participants infer healthfulness of foods across three very different food categories, in three reference amounts, using an FoP labelling scheme in which nutrition information is presented with and without percentage GDAs. GDA schemes express values for energy, sugar, fats, saturated fats and salt that a portion of the food contains as a percentage contribution to the daily requirements of an average reference adult.…”
Section: Introductionmentioning
confidence: 99%